Urbanization Negatively Affects the Species Composition of Native Ladybirds in Central Europe - Skuhrovec, Jiří; Honek, Alois; Martinkova, Zdenka (Frontiers in Conservation Science, 2021)
We evaluated the differences in frequency (percentage of sampling sessions where the species was recorded) and abundance (mean number of individuals per 100 sweeps) of native species of ladybirds (Coleoptera: Coccinellidae) in the center of Prague, Central Europe, and in its outskirts. Between 2016–2019, coccinellids were sampled on Tilia stands using a standardized sweeping method. Twenty-one species were identified in the total sample of 2761 adults that were collected in 504 sampling sessions. Species richness was significantly higher in the outskirts than in the center, where seven species were absent and two species were found only once. In contrast, only five species were more abundant in the center than in the outskirts. Communities of native coccinellids were poorer in species, and most species were less abundant in the center than in the outskirts.